EFFECT OF CAPITAL ADEQUACY AND LIQUIDITY MANAGEMENT ON FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Joseph Olorunfemi Akande (Gusau Journal of Accounting and Finance)
The financial performance of banks is crucial for economic stability, yet listed deposit money banks in Nigeria continue to face challenges in maintaining optimal capital adequacy and liquidity management. This study examines the effect of capital adequacy and liquidity management on the financial performance of listed deposit money banks in Nigeria, measured by Return on Equity (ROE). Using a correlational research design, secondary data were extracted from the financial statements of 10 listed deposit money banks on the Nigerian Exchange Group (NGX) from 2014 to 2023. A census sampling approach was employed to ensure comprehensive analysis. Data were sourced from audited financial reports, the Central Bank of Nigeria (CBN) Banking Supervision Reports, and other regulatory publications. The study employed panel data methodology and multiple regression analysis to evaluate the impact of capital adequacy and liquidity management on ROE. The findings revealed that both capital adequacy and liquidity management have a significant positive effect on financial performance, with liquidity management exhibiting a stronger influence. This suggests that banks with well-structured capital reserves and effective liquidity strategies achieve higher profitability and resilience. The study concludes that optimal capital adequacy and liquidity management are essential for sustaining financial performance and stability in the Nigerian banking sector. The study recommends among others that banks should enhance human capital development through periodic financial training for employees and clients, ensuring better financial decision-making and improved liquidity management practices.